CLINICAL AND PARACLINICAL CHARACTERISTICS AND SOME RELATED FACTORS IN PRIMIPAROUS FULL-TERM WOMEN WITH INDICATIONS FOR CESAREAN SECTION AT HAI DUONG OBSTETRICS HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical characteristics, paraclinical features, and selected related factors among full-term primiparous women indicated for cesarean section at Hai Duong Obstetrics Hospital.Research subjects and methods: A prospective cross-sectional descriptive study was conducted on 235 full-term primiparous pregnant women admitted to the hospital, of whom 137 women had indications for cesarean section at Hai Duong Obstetrics Hospital from October 1, 2024 to December 31, 2024.Results: Women aged 20–30 years accounted for the majority (79.2%). Most participants were self-employed (41.7%) or factory workers (30.6%), lived in urban areas (76.3%), and had a height greater than 150 cm (85.5%). The cesarean section rate among primiparous women was 58.3%. The main reason for hospital admission was abdominal pain (74.5%). Most women presented with cervical dilatation ≤ 2 cm (91.2%), infrequent uterine contractions (92.7%), normal amniotic fluid volume (90.5%), intact membranes (89.0%), normal placental position (99.3%), fetal heart rate of 120–160 beats per minute (95.6%), and neonatal birth weight ranging from 2500 to 3499 g (66.4%). Cesarean section due to two or more indications accounted for 19%, mainly related to fetal and fetal adnexal factors (84.0%). Women with a height of 145–150 cm had a significantly higher rate of cesarean section compared with vaginal delivery.Conclusion: The rate of cesarean section among first-time mothers was relatively high, mainly due to fetal and placental factors. Maternal height was significantly associated with the indication for cesarean section.
Keywords: Cesarean section, primiparous women